Outcomes of Asthmatic Children Clinic at Chaoprayayomraj Hospital - Watanarangsan, Pornchai (Journal of Health Science of Thailand, 2017)
The purpose of this propective descriptive research was to evalvate outcomes of a asthmatic children clinic in Chaoprayayomraj hospital. The duration of data collection were from August 1, 2010 to July 31, 2012 and the data analysis were presented in frequency, percentage. Correlation was established by Wilcoxon signed rank test at 0.05 level of significance. The asthma clinic team consisted of a doctor, a nurse and a pharmacist. The subjects were 63 asthmatic patients who visited this clinic since the first 2 months, and had been undergoing treatment through the two years that followed. This subjects had no other underlying diseases. The result showed that the patients were mostly male (58.7%), aged 5-10 years and reported with allergic rhinitis. The asthma control improved significantly from 60.3 to 79.4 and 98.4 percent among asthmatic patients at 1 and 2 year intervals. The admission rate decreased significantly from 1.89 to 0.29 and 0.03 visit/person/year at the same intervals. The Emergency Room visit decreased significantly also from 3.03 to 0.78 and 0.13 visit/person/year consecutively. There was no death or drug adversed event reported in this study. In conclusion, this findings reveals the favorable outcomes among asthmatic patients in the childhood asthma clinic which may be a good model for childhood asthma management by other hospitals.